Application of simulation and MCDEA in SME food processing company : a case study at a coffee processing factory - Nur Fathin Mohd Noor,; Ruzanita Mat Rani, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Food production in the manufacturing sector contributes significantly to the development of the Malaysian economy. Therefore, the improvement of food manufacturing should be emphasised so that it is possible to ensure its sustained growth. This study focuses on applying a simulation model and Multi-Criteria Data Envelopment Analysis (MCDEA) in the food manufacturing system. A case study on an SME food processing company was modelled and analysed to improve the system’s overall performance. In this study, simulation experiments and MCDEA were used to improve the processing system, and several improvement models were suggested. The simulation model of each improvement was used to generate inputs and outputs, while MCDEA was used to determine the most efficient improvement model to minimise waiting time. The result demonstrates that IM7 is the most efficient model as compared to other improvement models. This model suggests adding a worker into the packaging process and reducing processing time at grinding and packaging processes. The methods and the results obtained can assist the management of a factory in making better decisions and can offer insights to other SME companies to help improve the performance of their food processing system.